Expression and characterization of recombinant human phospholipid hydroperoxide glutathione peroxidase. Issue 11 (30th October 2013) - Han, Xiao; Fan, Zhenlin; Yu, Yang; Liu, Shaoli; Hao, Yazhou; Huo, Rui; Wei, Jingyan
Abstract Phospholipid hydroperoxide glutathione peroxidase (PHGPx or GPx4; EC1.11.1.12) is a selenoperoxidase that can directly reduce phospholipid and cholesterol hydroperoxides. The mature cytoplasmic GPx4 is a monomeric protein with molecular weight of 19.5 kDa. In this study, human GPx4 (hGPx4) gene was amplified from the complementary DNA library of human hepatoma cell line. Eukaryotic expression plasmid pSelExpress1‐leader‐GPx4 was constructed and transfected into the eukaryotic cells HEK293T. Expression of hGPx4 was detected by Western blotting, and the target protein was purified by immobilized metal affinity chromatography. The results of the activity and kinetics of the purified protein show that the obtained protein follows a "ping–pong" mechanism, which is similar to that of native cytosolic glutathione peroxidase (GPx1; EC1.11.1.9). This is the first time that hGPx4 could be expressed and purified from HEK293T cells, and this work will provide an important resource of hGPx4 for its functional study in vitro and in vivo. © 2013 IUBMB Life, 65(11):951–956, 2013